Kemampuan Membedakan Kalimat Fakta dan Opini Melalui Kegiatan Membaca Intensif Siswa Kelas X SMK-SMAK Padang - Sartika, Rina; Emidar, Emidar; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study were to (1) describe the ability of students to determine the sentence facts through intensive reading class X-SMAK SMK Padang, (2) describe the ability of students to determine the sentence opinions through intensive reading class X-SMAK SMK Padang, (3) describes the differences of students' ability to distinguish between fact and opinion sentences through intensive reading class X-SMAK SMK Padang. The data of this research is a test answer sheet that was held on December 6, 2012. Tests to be objective about the amount of about 30 grains of matter, which consists of 15 questions and 15 questions facts opinions. The data sources of this study are writing as a source of primary sources of the student-SMAK SMK Padang. Data collected view of providing intensive reading test paragraphs of the matter abjektif given researchers. The findings of the study showed that there is a difference in determining the sentence facts and opinions. The ability to determine the facts sentences (69.80%) and subjective (63.88%).